Clinico–anatomical characteristic of the traffic trauma in the megapolis environment.Second report: anatomical verification of injuries - S. O. Guryev; V. A. Kushnir; O. S. Solovyov (Клінічна хірургія)
Objective.Verification of clinic–anatomical characteristics of trauma as a consequence of traffic accident in the megapolis environment.